Analysis and Characterization of Solid and Liquid Organic Fertilizer from Hydrothermal Carbonization (HTC) of Chicken Feather and Blood Waste - Agus Kuncaka; Rizky Ibnufaatih Arvianto; Almas Shafira Ramadhanty Bunga Latifa; Munawir Ramadhan Rambe; Adhitasari Suratman; Sugeng Triono (Indonesian Journal of Chemistry, 2021)
Conversion of feather and blood from chicken slaughterhouse waste for producing solid and liquid organic fertilizer excluding composting process with a variation of the mass ratio of feather and blood of a chicken has been conducted. The nitrogen, sulfur, and iron content in the solid and liquid product of the hydrothermal carbonization process were analyzed to identify and characterize the possibility of hydrolysate as a source of nitrogen, sulfur, and iron in soil fertilizer. Feather and blood of chicken waste were introduced to a hydrothermal carbonization reactor with the addition of limestone at a temperature range of 160–170 °C for the preparation of solid and liquid organic fertilizer. According to the FTIR interpretation, the solid product had functional groups such as NH, OH, CH sp3, SH, C=O, C=C, C–O–C, and C–H aromatic. The nitrogen, sulfur, and iron content of the optimal ratio in the solid phase were 4.67%, 1.63%, and 3694.56 ppm, while their contents in the liquid fertilizer were 3.76%, 1.80%, and 221.56 ppm, respectively. The vibration of 478 cm–1 is attributed to Fe–O paramagnetic (Fe2O3) confirmed by TEM images showed the diameter size less than 20 nm indicating the presence of superparamagnetic material.